Advances in Multidisciplinary Retrieval First Information Retrieval Facility Conference, IRFC 2010, Vienna, Austria, May 31, 2010, Proceedings - Cunningham, Hamish; Hanbury, Allan; Rüger, Stefan (Information Systems and Applications, incl. Internet/Web, and HCI, 2010)
These proceedings contain the refereed papers and posters presented at the ?rst Information Retrieval Facility Conference (IRFC), which was held in Vienna on 31 May 2010. The conference provides a multi-disciplinary, scienti?c forum that aims to bring young researchers into contact with industry at an early stage. IRFC 2010 received 20 high-quality submissions, of which 11 were accepted and appear here. The decision whether a paper was presented orally or as poster was solely based on what we thought was the most suitable form of communi- tion, considering we had only a single day for the event. In particular, the form of presentation bears no relation to the quality of the accepted papers, all of which were thoroughly peer reviewed and had to be endorsed by at least three independent reviewers. The Information Retrieval Facility (IRF) is an open IR research institution, managedby a scienti?c board drawnfrom a panel of internationalexperts in the ?eldwhoseroleistopromotethehighestqualityintheresearchsupportedbythe facility. As a non-pro?t research institution, the IRF provides services to IR s- ence in the form of a reference laboratory,hardwareand softwareinfrastructure. Committed to Open Science concepts, the IRF promotes publication of recent scienti?c results and newly developed methods, both in traditional paper form and as data sets freely available to IRF members. Such transparency ensures objective evaluation and comparabilityof results and consequently diversity and sustainability of their further development.